2016
DOI: 10.3389/fpubh.2016.00195
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Demographic, Socioeconomic, and Psychological Factors on Glycemic Self-Management in Adults with Type 2 Diabetes Mellitus

Abstract: Diabetes mellitus (DM) is reported as one of the most complex chronic diseases worldwide. In the United States, Type 2 DM (T2DM) is the seventh leading cause of morbidity and mortality. Individuals with diabetes require lifelong personal care to reduce the possibility of developing long-term complications. A good knowledge of diabetes risk factors, including obesity, dyslipidemia, hypertension, family history of DM, and sedentary lifestyle, play an essential role in prevention and treatment. Also, sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 58 publications
8
57
2
5
Order By: Relevance
“…A significant association between the risk of AD and lower education level was also observed that corroborated in present findings [57]. Other findings also indicated significant association between T2DM group, age, education, and area of locality [58,59,60], that matched our observation. These demographic parameters directly or indirectly are associated with T2DM and AD.…”
Section: Discussionsupporting
confidence: 92%
“…A significant association between the risk of AD and lower education level was also observed that corroborated in present findings [57]. Other findings also indicated significant association between T2DM group, age, education, and area of locality [58,59,60], that matched our observation. These demographic parameters directly or indirectly are associated with T2DM and AD.…”
Section: Discussionsupporting
confidence: 92%
“…The mental symptoms were correlated positively with the duration of the diabetes diagnosis, being significantly higher among Type 2diabetes patients with an established disease when compared with newly diagnosed patients. However, there was no significant correlation between HbA1c levels and mental health [30,35].The same as our results showed that HbA1c had little influence on mental health. These findings also indicated that HbA1c had no statistically significant effects on environmental QoL.…”
Section: Discussionsupporting
confidence: 75%
“…Some studies have demonstrated that women are more likely to have better glycemic control compared to men, whereas other studies have shown the opposite [36,37]. This may be related to different cultural and social norms, such as sex role and the importance of family [30,38].This study indicated that sex and physical health were correlated. These results were consistent with the findings of earlier research [5].…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Good knowledge about the risk factors of diabetes including age, gender, educational level, the area of residence, BMI, and obesity, family history, and inactive life-style, plays an essential role in prevention and treatment [6]. Also, financial, psychological, and ecological features are directly and indirectly linked with diabetes management and treatment results [7]. [8].…”
Section: Introductionmentioning
confidence: 99%